2021
DOI: 10.13057/biodiv/d220646
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth pattern, condition factor, gonadosomatic index of Manggabai (Glosogobius giuris) and Payangka (Ophieleotris aporos) in Limboto Lake, Gorontalo, Indonesia

Abstract: Abstract. Hasim, Tuheteru J, Fazrin DN. 2021. Comparison of growth pattern, condition factor, gonadosomatic index of Manggabai (Glosogobius giuris) and Payangka (Ophieleotris aporos) in Limboto Lake, Gorontalo, Indonesia. Biodiversitas 22: 3388-3393. Manggabai and Payangka are endangered native fishes in Limboto Lake due to continuous degradation in the lake. In addition, silting lake along with its area that continues to narrow can threaten the life of both fishes although the government has stipulated restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, this study revealed no isometric growth patterns were found in M. gulio, as stated in the study by Gupta (2014). Therefore in this study, the growth pattern of M. gulio based on sex, time, and location generally showed an allometric growth pattern, similar to the research by Hasim et al (2021) and Verma and Prakash (2019) that the growth pattern of M. gulio is allometric.…”
Section: Length-weight Relationshipssupporting
confidence: 88%
See 3 more Smart Citations
“…However, this study revealed no isometric growth patterns were found in M. gulio, as stated in the study by Gupta (2014). Therefore in this study, the growth pattern of M. gulio based on sex, time, and location generally showed an allometric growth pattern, similar to the research by Hasim et al (2021) and Verma and Prakash (2019) that the growth pattern of M. gulio is allometric.…”
Section: Length-weight Relationshipssupporting
confidence: 88%
“…The b value explains the growth pattern of fish; if the value of b > 3 indicates a positive allometric growth pattern, b < 3 is negative allometric, and b = 3 isometric (Hasim et al 2021). However, this study revealed no isometric growth patterns were found in M. gulio, as stated in the study by Gupta (2014).…”
Section: Length-weight Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bamboo can help fishermen's livelihoods because it can be used as a traditional fishing tool (Hasim et al 2021). Bamboo is also used as a drying container for Kappaphycus alvarezii seaweed collected from farmers in North Gorontalo (Katili et al 2019).…”
Section: Helps Livelihoodsmentioning
confidence: 99%